(untitled) (Studia Prawnicze / The Legal Studies, 2016)
The article undertakes to analyze the problem of delivery of the judgment by default with particular emphasis on the issue of the subsequent submission of the statement of opposition that judgment. In view of the fact that often plaintiff deliberately indicates an incorrect address of the defendant, which means that he has no knowledge of the judgment by default and his right to a court is then significantly reduced the author proposes to introduce sanctions for the plaintiff acting in this way.